The Role of Innovations in Modern Economy - Djalilova Nigora Mavlonovna (International Journal on Economics, Finance and Sustainable Development, 2022)
In this article, innovation is becoming one of the most characteristic features of economic development and is analyzed as a factor accelerating the development of the market. Also we have given our suggestions and recommendations, today’s world through the widespread use of innovation.